A new species of the leafhopper genus Bhatia Distant (Hemiptera: Cicadellidae: Deltocephalinae) from China - Lu, Lin; Zhang, Yalin (Zootaxa, 2015)
A new leafhopper species Bhatia multispinosa Lu & Zhang is described from the Emei Mountains in China. A checklist to the species of Bhatia Distant from China is provided, together with a key for their separation.